Sentarum langurs (Presbytis chrysomelas) demographic parameters in Sepandan Resort Area of Sentarum Lake National Park - samsul, samsul; Samsul; Santoso, Nyoto; Mas’yud, Burhanuddin (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Lutung Sentarum (Presbytis Chrysomelas spp cruciger) is a member of the Presbyis tribe. Langur Sentarum (Presbytis Chrysomelas Cruciger) is one of the endemic animals in West Kalimantan with unprotected status, but is vulnerable to extinction. The study was conducted to obtain data on the demographic parameters of animal populations and their management in the Sepandan Resort area. The research was conducted through field observations to obtain data on demographic parameters with the concentration count method based on consideration of the characteristics of species distribution and field conditions in the research area. Population size data collection was carried out at 15 observation points, which were spread across all habitats types in the research study area. Observations or population size calculations at one point were carried out three times, namely in the morning (06.00 – 08.00), afternoon (12.00 – 14.00) and afternoon (16.00 – 18.00), and three replicates were carried out. The results of data from Lutung sentarum at the Sepandan resort found 8 groups from 2 areas, namely in Pelaik hamlet 2 groups and in Kedungkang hamlet 6 groups. Each group relatively had 1 adult male. Total individuals found were 58 individuals consisting of: 8 adult males, 25 adult females, 5 juvenile males, 18 juvenile females and 2 chicks. The total number of adult males and juveniles is 13 individuals and the total number of females is 43 individuals. The results in the sex ratio calculation of the encounter of 8 groups consisting of 13 males and 43 females were composed of sex ratio values of 1: 3. Total natality value of 8 groups of langur sentarum is 0.08.